If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-6=2+5x^6x
We move all terms to the left:
-6-(2+5x^6x)=0
We do not support expression: x^6x
| –12=6w+6 | | 3(m+5)-6=3m+9 | | 2(x+3)=5(x-4)+8 | | 5x-2(x-4)=-2+5x-2 | | 3x+2x-4=4 | | 5r^2-8r+10=-2 | | x/2=2.5=5 | | 0=−30t^2+30t+1. | | 7x-2x=5x+14 | | 8=−30t^2+30t+1. | | 10x-1.8-2=7x-1.8-7.4 | | 5x-7=9.47 | | 4/9+4(x+1)=28/9-(x-7x)+1 | | -5x+32-20x+4x=180 | | x+5/8=-8.3 | | 9-5x=-40 | | x/5=6.4 | | 7m+8=3m-1 | | 3x-14=-5x+21 | | 0.75+4=0.5x+9 | | 5×(x+3)=2x-3 | | 23x=1611 | | S-1.7x=4.6 | | 6x+2+5x+2=180 | | -9x+9=-12x+6 | | 7y=8+3+3= | | (5-x)2=25 | | 45=26+x | | -18+3x=-4x+50 | | 2.50x=1x+15 | | x-8/11=2/11 | | 3x+2+83=90 |